Plaque index and gingival index during rapid maxillary expansion of patients with unilateral cleft lip and palate - Maria Olívia Rocha; Dauro Douglas Oliveira; Fernando Oliveira Costa; Laíze Rosa Pires; Amanda Rafaela Diniz; Rodrigo Villamarim Soares
ABSTRACT Objective: To assess, during rapid maxillary expansion, the plaque index (PI) and the gingival index (GI) of patients with unilateral cleft lip and palate(UCLP) using Hyrax (HX) or inverted mini-Hyrax (IMHX) rapid maxillary expanders (RME) considering patients' sex and age. Methods: PI (Quigley Index modified by Turesky et al) and GI (Löe and Silness) of 28 UCLP (11 females; 17 males: aged 8 to 15 years) submitted to daily RME activation were assessed before (T0) and 7 (T1), 28 (T2) and 90 (T3) days after activation. Log-linear models and Bonferroni correction were performed to analyze possible differences in PI and GI between RME, sexes or age groups over time. Results: Intra-group comparison revealed significant increases in PI of patients using HX (T0 < T2), IMHX (T0 < T3; T1< T3), males (T0 < T1; T0 < T2; T0 < T3) or aged 12-15 years (T0 < T1; T0 < T2; T0 < T3), and in GI of patients using IMHX (T0 < T3; T1 < T3), females (T1 < T3; T2 < T3) or aged 12-15 years (T0 < T3; T2 < T3). One inter-group difference in GI according to patients' age (8-11 < 12-15; T1) was observed. Conclusions: Since a single difference between groups was encountered, the results of this study indicated that PI and GI during maxillary expansion were similar between HX and IMHX, sexes and the analyzed age groups. Therefore, orthodontists can use these RME in UCLP patients according to the patient's necessity or their preferences.